2021
DOI: 10.21037/qims-20-1141
|View full text |Cite
|
Sign up to set email alerts
|

Prior information guided auto-contouring of breast gland for deformable image registration in postoperative breast cancer radiotherapy

Abstract: Background: Contouring of breast gland in planning CT is important to postoperative radiotherapy of patients after breast conserving surgery (BCS). However, the contouring task is difficult because of the poorer contrast of breast gland in planning CT. To improve its efficiency and accuracy, prior information was introduced in a 3D U-Net model to predict the contour of breast gland automatically.Methods: The preoperative CT was first aligned to the planning CT via affine registration. The resulting transform w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Manual segmentation of all images is generally used in radiomics studies, especially in MRI scans ( 44 ). The segmentation of prior knowledge regions we applied to knee OA DL models was influenced by the work of Hosseinzadeh et al and Xie et al ( 19 , 45 ), who concluded that prior zonal knowledge significantly affected the performance of DL models. Finally, we proved that the DL model established in this study performed better than did experienced radiologists, which indicates that the model could be a tool to help clinicians make accurate diagnoses and treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Manual segmentation of all images is generally used in radiomics studies, especially in MRI scans ( 44 ). The segmentation of prior knowledge regions we applied to knee OA DL models was influenced by the work of Hosseinzadeh et al and Xie et al ( 19 , 45 ), who concluded that prior zonal knowledge significantly affected the performance of DL models. Finally, we proved that the DL model established in this study performed better than did experienced radiologists, which indicates that the model could be a tool to help clinicians make accurate diagnoses and treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure can potentially be improved by other novel methods or deep learning methods in terms of precision and efficiency. [37][38][39] Fourth, the slice resolution of CT image in this study was limited to 5 mm due to clinical protocol. A finer thickness (<3 mm) will result in better registration accuracy, where the improvement is marginal with 1 mm according to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the traditional automatic methods for point detection (Harris Corner Detection) and contour segmentation (gray‐level thresholding segmentation) were less accurate, especially in low contrast regions. This procedure can potentially be improved by other novel methods or deep learning methods in terms of precision and efficiency 37–39 . Fourth, the slice resolution of CT image in this study was limited to 5 mm due to clinical protocol.…”
Section: Discussionmentioning
confidence: 99%
“…All CTs were pre-processed using 3D Slicer (RRID:SCR_005619) [ 13 , 14 ]. They were first resampled to an isotropic resolution of 1 × 1 × 5 mm and then cropped to dimensions of 256 × 256 × 32 around the breast's centroid [ 15 ].…”
Section: Methodsmentioning
confidence: 99%